Cotton Solidarity Policy In The Country Of Turkey During The Period Of Strong Soviet Rule - B.U.Bokiyev; F.M.Mirzayeva (Indonesian Journal Publisher, 2025)
This research investigates the Soviet-era cotton policy in Turkey, focusing on land reforms, water management, and agricultural development under Soviet influence. The study employs a historical-documentary analysis method, reviewing legislative acts, economic reports, and archival materials. Findings indicate that Soviet policies significantly transformed agricultural production, introducing state-controlled cotton industries and centralized irrigation projects. The research provides insights into economic restructuring and its long-term effects on regional agriculture.